A geometrical optimisation of a coplanar micro-electrode structure for microfluidic flow cytometry - Van Phu Nguyen; Van-Anh Bui; Thu Hang Nguyen; Van Thanh Pham; Thi Thanh Thuy Dang; Quang Loc Do (Vietnam Journal of Science, Technology and Engineering)
Single-cell analysis provides a more information-rich approach to disease diagnosis than traditional methods. At the cellular level, electrical properties have been established as reliable disease markers, capable of revealing variations between individual cells. This study focuses on optimising the geometry of a coplanar micro-electrode structure for detecting human lung adenocarcinoma cells (A549) within a fluid channel using impedance flow cytometry. A549 cells were chosen due to their frequent occurrence in cancer cases and the extensive documentation of their electrical properties and size. To further investigate the electric field and optimise the electrode design for single-cell detection, a numerical 3D model based on the finite element method (FEM) was developed and implemented. The functionality of the sensing structure was validated using COMSOL Multiphysics, with the Electric Current module defining scalar electric potential within the 3D model. Simulations explored various parameters, including electrode dimensions, frequency range, object sizes, and electrical conductivity, to fine-tune the sensor’s performance. Additionally, the study elucidates the impact of cell position within the channel structure and cell size on impedance measurements. This numerical investigation provides insights into the acquired impedance signals, contributing to the optimisation and standardisation of the device. The proposed sensor system holds significant potential across various applications in biomedicine and chemistry, particularly in point-of-care scenarios, where the sensor chip can be conveniently configured for measurements and discarded after use.